2011
DOI: 10.1002/adem.201000282
|View full text |Cite
|
Sign up to set email alerts
|

A Role of α′ Martensite Introduced by Thermo‐Mechanical Treatment in Improving Shape Memory Effect of an Fe‐Mn‐Si‐Cr‐Ni Alloy

Abstract: The evolution of α′ martensite with different thermo‐mechanical treatment and its effect on the shape memory effect were studied in an Fe‐14Mn‐5Si‐8Cr‐4Ni alloy. The α′ martensite was introduced by only 5% pre‐deformation, and its amount increased with increasing pre‐deformation up to 20%. The α′ martensite started to transform into austenite when the annealing temperature was 773 K. As the annealing temperature increased to 1 073 K, the α′ martensite almost transformed fully into austenite. The α′ martensite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…One is the transformation of face‐centered cubic (FCC) γ austenite to hexagonal close‐packed (HCP) ϵ martensite, and the other is the ϵ martensite to body‐centered cubic (BCC) α ′ martensite . Studies showed that only stress‐induced FCC → HCP martensite and its reverse transformation are responsible for the SME of Fe – Mn – Si‐based SMAs, the occurrence of γ (FCC) → ϵ (HCP) → α ′ (BCC) deteriorates the SME, which will be discussed in another section. Note that FCC → HCP martensitic transformation in Fe – Mn – Si‐based SMAs is non‐thermoelastic, in which a much bigger thermal‐hysteresis of above 100 K exists .…”
Section: Origin Of Sme In Fe–mn–si‐based Smasmentioning
confidence: 99%
See 2 more Smart Citations
“…One is the transformation of face‐centered cubic (FCC) γ austenite to hexagonal close‐packed (HCP) ϵ martensite, and the other is the ϵ martensite to body‐centered cubic (BCC) α ′ martensite . Studies showed that only stress‐induced FCC → HCP martensite and its reverse transformation are responsible for the SME of Fe – Mn – Si‐based SMAs, the occurrence of γ (FCC) → ϵ (HCP) → α ′ (BCC) deteriorates the SME, which will be discussed in another section. Note that FCC → HCP martensitic transformation in Fe – Mn – Si‐based SMAs is non‐thermoelastic, in which a much bigger thermal‐hysteresis of above 100 K exists .…”
Section: Origin Of Sme In Fe–mn–si‐based Smasmentioning
confidence: 99%
“…First, the occurrence of γ (FCC) → ϵ (HCP) → α ' (BCC) martensitic transformation depends on the Mn content and deformation strain in Fe – Mn – Si‐based SMAs . The α ' martensite is generally formed at the intersections between different orientation HCP martensite . Hoshino et al observed that the α ' martensite at the intersections of HCP martensite resulted in the increase of HCP → FCC reverse transformation temperature by in situ TEM .…”
Section: Effect Of Mn Content On Recovery Strains In Fe–mn–si‐based Smasmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] In 1986, Murakami and coworkers developed polycrystalline Fe- (28)(29)(30)(31)(32)Mn-(4-6.5)Si alloys showing almost complete SME as well. [3] In 1991, Otsuka et al developed Fe- (14)(15)(16)(17)(18)(19)(20)(21)(22)Mn-(5-6)Si- (8)(9)(10)(11)(12)Cr-(5-7)Ni alloys exhibiting good SME along with good corrosion resistance through alloying with Ni and Cr. [4] Thereafter, much research has been carried out on these Fe-Mn-Si-based alloys to further improve their recovery strain, including training, [5][6][7][8] thermo-mechanical treatment, [9][10][11] ausforming, [12,13] and precipitation of second-phase particles.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal defects and internal stress field could be introduced by cold pre‐deformation. Actually, a great number of recent studies have been focused on the effect of pre‐deformation on the properties of various materials, including aluminum alloy, Zirconium alloy, shape memory alloys, FeMn damping alloy and Mn‐15 at% damping alloy . In all, the defects and internal stress distribution aroused by the pre‐deformation play a critical role in affecting the properties of the above alloys.…”
Section: Introductionmentioning
confidence: 99%